Pathological Disorders Caused by Atmospheric Nanoparticles: Review - Ozdan Akram Ghareeb; Qahtan Adnan Ali (Peerian Journals Publishing, 2024)
Nanoparticles (NPs) arouse the interest of researchers around the world because of their ability to induce toxicity in vital organs of the body. These particles are considered one of the most important air pollutants because they remain suspended in the atmosphere for a long time and thus can travel over wide distances due to their extremely small size. NPs are able to effectively reach the bloodstream, cell membrane barriers, settle in organs and tissues, and even penetrate the bloodbrain barrier and reach the brain. These particles can cause pathological disorders in the respiratory, cardiovascular, and nervous systems. Due to the lack of relatively adequate archived data related to human exposure to nanoparticles in the atmosphere and their negative effects on health, there is an urgent need to clarify this to contribute to controlling human exposure to nanoparticles in toxic doses. Therefore, this scientific paper reviews the potential pathological effects of inhaled atmospheric nanoparticles on the body.
Keywords: Nanoparticles; pathological disorders; atmosphere